Rebamipide Improves Chronic Inflammation in the Lesser Curvature of the Corpus after Helicobacter pylori Eradication: A Multicenter Study. (28th April 2015) - Kamada, Tomoari; Sato, Motonori; Tokutomi, Tadashi; Watanabe, Tetsuo; Murao, Takahisa; Matsumoto, Hiroshi; Manabe, Noriaki; Ito, Masanori; Tanaka, Shinji; Inoue, Kazuhiko; Shiotani, Akiko; Akiyama, Takashi; et al.
Abstract : Background and Aim . Although many epidemiologic studies have shown that Helicobacter pylori eradication has prophylactic effects on gastric cancer, it does not completely eliminate the risk of gastric cancer. We aimed to investigate the changes in histological gastritis in patients receiving rebamipide treatment after H. pylori eradication. Methods . 206 patients who had undergone H. pylori eradication were evaluated. Of these, 169 patients who achieved successful eradication were randomly allocated to 2 groups: the rebamipide group ( n = 82) and the untreated group ( n = 87). The primary endpoints were histopathological findings according to the updated Sydney system at the start of the study and after 1 year. Results . Final assessment for histological gastritis was possible in 50 cases from the rebamipide group and 53 cases from the untreated group. The activity and atrophy improved in both the rebamipide and untreated groups, and no significant intergroup differences were observed. Chronic inflammation affecting the lesser curvature of the corpus was significantly improved in the rebamipide group compared to in the untreated group (1.12 ± 0.08 versus 1.35 ± 0.08 ; P = 0.043). Conclusions . Rebamipide treatment after H. pylori eradication alleviated chronic inflammation in the lesser curvature of the corpus compared to that in the untreated group. This trial is registered with UMIN000002369 .